Photocurrent response of B12As2 crystals to blue light, and its temperature-dependent electrical characterizations - Gul, R.; Cui, Y.; Bolotnikov, A. E.; Camarda, G. S.; Egarievwe, S. U.; Hossain, A.; Roy, U. N.; Yang, G.; Edgar, James H.; Nwagwu, U.; James, R. B. (My University, 2016)
With the global shortage of He-3 gas, researchers worldwide are looking for alternative materials for detecting neutrons. Among the candidate materials, semiconductors are attractive because of their light weight and ease in handling. Currently, we are looking into the suitability of boron arsenide (B12As2) for this specific application. As the first step in evaluating the material qualitatively, the photo-response of B12As2 bulk crystals to light with different wavelengths was examined. The crystals showed photocurrent response to a band of 407- and 470- nm blue light. The maximum measured photoresponsivity and the photocurrent density at 0.7 V for 470 nm blue light at room temperature were 0.25 A.W-1 and 2.47 mA.cm(-2), respectively. In addition to photo current measurements, the electrical properties as a function of temperature (range: 50-320 K) were measured. Reliable data were obtained for the low-temperature I-V characteristics, the temperature dependence of dark current and its density, and the resistivity variations with temperature in B12As2 bulk crystals. The experiments showed an exponential dependence on temperature for the dark current, current density, and resistivity; these three electrical parameters, respectively, had a variation of a few nA to mu A, 1-100 mu A.cm(-2) and 7.6x10(5)-7.7x10(3) Omega.cm, for temperature increasing from 50 K to 320 K. The results from this study reported the first photoresponse and demonstrated that B12As2 is a potential candidate for thermal-neutron detectors. (C) 2016 Author(s).
Citation: Gul, R., Cui, Y., Bolotnikov, A. E., Camarda, G. S., Egarievwe, S. U., Hossain, A., . . . James, R. B. (2016). Photocurrent response of B12As2 crystals to blue light, and its temperature-dependent electrical characterizations. Aip Advances, 6(2), 6. doi:10.1063/1.4941937
Keywords: Science & Technology - Other Topics; Materials Science; Physics